Harmful Fisheries Subsidies in Southeast Asia (ASEAN) - Wen, Chiat Lee; Viswanathan, K. Kuperan (2016)
Fisheries subsidies are crucial to the poor small scale fishers in Southeast Asia (ASEAN) as the fishers depend the subsidies for a living. However, the fisheries subsidies might also bring harm to the fisheries resources as the fishers use the fisheries subsidies to build the capacity to catch more fish. There is more than five million fishers in ASEAN and 90 percent of fishers are poor. The poor fishers need to be assisted by the ASEAN government to increase the livelihood. ASEAN government give away many subsidies to the fishers every year. The fishers in the top 6 ASEAN nations receive $3.3 billion of subsidies in year 2011 alone and 64 percent are allocated for harmful subsidies. The harmful subsidies should be avoided and fisheries subsidies should be managed well to ensure sustainability of fisheries resources in the long run. In this paper, we discuss the current status of harmful fisheries subsidies in ASEAN and recommend ways to balance between increasing livelihood of ASEAN fishers and ensure sustainability of fisheries resources in ASEAN seawaters. The ways recommended are relocation of small scale fishers to aquaculture, co-management and deep sea aquaculture that involves government.